The genus Sphegina Meigen (Diptera, Syrphidae) in a biodiversity hotspot: the thirty-six sympatric species in Kambaiti, Myanmar - Hippa, Heikki; Steenis, Jeroen Van; Mutin, Valeri A. (Zootaxa, 2015)
The material of Sphegina collected by René Malaise in Kambaiti, Myanmar, in 1934 includes S. (Sphegina) kumaoniensis Mutin and the following 35 new species: S. (Sphegina) uncinata, S. (Asiosphegina) achaeta, S. (A.) adusta, S. (A.) atricolor, S. (A.) bidens, S. (A.) bilobata, S. (A.) carinata, S. (A.) cerina, S. (A.) crassispina, S. (A.) crucivena, S. (A.) culex, S. (A.) cultrigera, S. (A.) ensifera, S. (A.) falcata, S. (A.) forceps, S. (A.) forficata, S. (A.) furva, S. (A.) gigas, S. (A.) index, S. (A.) malaisei, S. (A.) minuta, S. (A.) mirifica, S. (A.) nasuta, S. (A.) pollex, S. (A.) pollinosa, S. (A.) parvula, S. (A.) pusilla, S. (A.) radula, S. (A.) raduloides, S. (A.) siculifera, S. (A.) simplex, S. (A.) sinesmila, S. (A.) subradula, S. (A.) trichaeta and S. (A.) trispina. A key to the studied species is given. The world fauna of Sphegina now comprises 120 species.